Pengaruh Perilaku Teman Sebaya, Penggunaan Media Sosial, dan Gaya Hidup Terhadap Perilaku Konsumtif Siswa-Siswi SMKN 1 Tanjung Jabung Barat Tahun Ajaran 2023/2024 - Siti Hartina; Ahsan Putra Hafiz; Nurlia Fusfita (Journal Economic Excellence Ibnu Sina, 2024)
Consumptive behavior can be said to be the behavior of buying goods without strong consideration and prioritizing desires over needs. Consumptive behavior is influenced by two main factors, including internal factors that cause consumptive behavior including self-esteem, drive, self-concept, and personality. As well as external factors that cause consumer behavior due to social class, culture, reference groups and family. This research aims to determine the influence of peer behavior, use of social media, and lifestyle on the consumptive behavior of students at SMKN 1 Tanjung Jabung Barat for the 2023/2024 academic year. The method in this research is quantitative research. The samples were taken using nonprobability techniques. The sample in this research were class The analysis used is multiple linear regression with the SPSS 27 program. The research results show that peer behavior (X1) partially influences consumptive behavior (Y), social media (X2) partially has no influence on consumptive behavior (Y), lifestyle (X3) partially influences consumptive behavior (Y). Meanwhile, simultaneously the behavior of peers, social media and lifestyle on consumer behavior is 32.9%. And the remaining 67.1% is influenced by other variables outside this research.